Exploring dentists' preferences for post-endodontic restorations in India: A questionnaire based study - Reetika Singh; Sachin Gupta; Vineeta Nikhil; Shikha Jaiswal (Wolters Kluwer Medknow Publications, 2024)
Aim: This study aimed to investigate the selection of postendodontic restorative materials and techniques for both anterior and posterior teeth by Indian endodontists and nonendodontists, along with other influencing factors. Methods: A total of 700 dentists, including both endodontists and nonendodontists, participated in this survey. The survey consisted of 22 questions and was administered through Google Forms and various online platforms. Participants were required to provide informed consent before completing the questionnaire. Results: The majority of endodontists (80.3%) and nonendodontists (72.6%) revealed a preference for resin composite as the primary restorative material for postendodontic restoration. Approximately half of the endodontists (50.0%) and 67.8% of nonendodontists typically waited for 1 week before proceeding with postendodontic restoration, with the presence of periapical lesions being the most common reason for this delay. Both endodontists (81.7%) and nonendodontists (73.4%) considered the amount of remaining tooth structure as the most crucial factor in guiding their choice of postendodontic restoration. The majority of both endodontists (75.3%) and nonendodontists (81.4%) preferred full-coverage crowns as the definitive postendodontic restoration. Furthermore, endodontists (95.4%) and nonendodontists (85.5%) reported that they only performed post and core restoration when necessary, and 84.7% of endodontists and 76.5% of nonendodontists believed that post and core restorations aided in supporting crowns. Conclusion: The outcomes of the survey imply that while endodontists in India demonstrate a more comprehensive comprehension of postendodontic restoration concepts, nonendodontists also exhibit a sufficient level of understanding essential for achieving clinical success.